Development of Caesarean Section Clinical Pathway : a lesson learnt - Sastrawan, I Gede (Fakultas Kedokteran Universitas Brawijaya)
Clinical pathway is a crucial clinical management strategy aimed to ensure quality and cost. However, the development of clinical pathway at the hospital was mainly for administrative purpose as it is required by accreditation standards leading to high variation. Study aims to develop clinical pathway for caesarean section and explore the problem during development and initial implementation (simulation). The selection of caesarean section is based on its high volume, risk, and cost. Using participatory action research, the researcher started the program by performing literature review and regulation to proposed the first revised version draft. A group of relevant expert in the hospitals than discuss and proposed review, considering the available resources, current practice and behavior. The main differences of the new clinical pathway are: 1) it was developed based on literature and current practice, 2) adding notification, explanation, inclusion and exclusion criteria, and references.Â Before initial implementation (simulation), the hospital also develop a procedure operational standards for the implementation, resources, and monitoring.Â The first simulation on two cases found differences in type of medication and documentation method, which than further discussed with all care providers involved to define the agreed solution. Professional engagement and openness culture that embrace along the process are the main important key lesson learnt in addition to the understanding that clinical pathway development and implementation is a continuous learning process. Therefore continuous monitoring and evaluation is of paramount important to reach quality and efficiency, the ultimate goals of clinical pathway.